REVEALING A JAVANESE IDENTITY OF PRAYER IN THE WEDHATAMA THROUGH SEMANTIC PROPOSITION - Tantri Refa Indhiarti; Sri Utami Budi; Indah Winarni (Universitas Muhammadiyah Surakarta, 2017)
The Wedhatama, a Javanese literary work by the King Mangkunegara IV contains philosophical teachings which are quite influential in ethical life. This paper aims at discovering the hidden meaning of the teachings which reveal an esoteric knowledge of worshipping in terms of its semantic point of view. This meaning is known through analytic and synthetic propositions in Gambuh canto associated with 4 different types of worship. Thus, the qualitative paradigm is used in which the data were obtained through library research. In this study, the synthetic proposition shows the breadth of the poet’s signifying esoteric intention that is about Javanese identity of prayer. It is revealed that the four types of worship –sembah raga, cipta, jiwa, and rasa –are said to coincide with what are usually referred to in Muslim Sufism as syariat. Keywords: Gambuh canto, the Wedhatama, Javanese identity of prayer, semantic proposition